2014
DOI: 10.1177/1527002514556719
|View full text |Cite
|
Sign up to set email alerts
|

Market Competition and Threshold Efficiency in the Sports Industry

Abstract: Previous studies of competitive balance (CB) have analyzed the variations in game outcomes that is the second moment of winning percentage. This article differs in two aspects. First, it analyzes market competition with respect to efficiency. Second, it analyzes efficiency distribution (in particular, the third moment of the efficiency distribution and the efficiency bound). It also suggests the efficiency bound as a new measure of market competition. By applying stochastic frontier models to a panel data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…For example, the analysis and testing of Rottenberg's "uncertainty of outcome hypothesis" seeks to determine the impact of competitive balance on fan demand (see the surveys in * This work was supported by the National Research Foundation of Korea Grant funded by the Korean Government (NRF-2016S1A2A2912186 Fort and Quirk (1995), citing Mandelbrot (1963Mandelbrot ( , 1967) and then Fama (1963Fama ( , 1965 and Fama and Roll (1968a, 1968b, 1971 in the finance literature, tested normality against non-normal stable distributions for winning percentage, but only for MLB , NBA (1975/76-1992/93), and NFL (1930-1941. Lee, Jang, and Hwang (2015) compared the win production efficiency distributions of four European football leagues and found that symmetry of the distribution is different across leagues. Groot (2008) argues for, and applies the Poisson distribution to winning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the analysis and testing of Rottenberg's "uncertainty of outcome hypothesis" seeks to determine the impact of competitive balance on fan demand (see the surveys in * This work was supported by the National Research Foundation of Korea Grant funded by the Korean Government (NRF-2016S1A2A2912186 Fort and Quirk (1995), citing Mandelbrot (1963Mandelbrot ( , 1967) and then Fama (1963Fama ( , 1965 and Fama and Roll (1968a, 1968b, 1971 in the finance literature, tested normality against non-normal stable distributions for winning percentage, but only for MLB , NBA (1975/76-1992/93), and NFL (1930-1941. Lee, Jang, and Hwang (2015) compared the win production efficiency distributions of four European football leagues and found that symmetry of the distribution is different across leagues. Groot (2008) argues for, and applies the Poisson distribution to winning.…”
Section: Introductionmentioning
confidence: 99%
“…Fort and Quirk (), citing Mandelbrot (, ) and then Fama (, ) and Fama and Roll (, , ) in the finance literature, tested normality against non‐normal stable distributions for winning percentage, but only for MLB (1952–1985), NBA (1975/76–1992/93), and NFL (1930–1941). Lee, Jang, and Hwang () compared the win production efficiency distributions of four European football leagues and found that symmetry of the distribution is different across leagues. Groot () argues for, and applies the Poisson distribution to winning.…”
mentioning
confidence: 99%